2012
DOI: 10.1093/her/cys105
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing community knowledge and health behaviors to eliminate blinding trachoma in Mali using radio messaging as a strategy

Abstract: The National Blindness Prevention Program in Mali has broadcast messages on the radio about trachoma as part of the country's trachoma elimination strategy since 2008. In 2011, a radio impact survey using multi-stage cluster sampling was conducted in the regions of Kayes and Segou to assess radio listening habits, coverage of the broadcasts, community knowledge and behavior specific to trachoma and facial cleanliness of children. Radio access and listening were high, with 60% of respondents having heard a mess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Tailoring educational materials to the specific sociocultural context, including use of non-textual media to include individuals with low literacy skills, may further enhance education uptake in endemic communities. The use of locally-broadcast radio programs or simple, illustrative printed material such as posters, leaflets and comic books may also add value to educational programs [7, 8, 11, 37], especially in areas where access to smartphones or computers is limited. Some standardized educational posters are available for T .…”
Section: Discussionmentioning
confidence: 99%
“…Tailoring educational materials to the specific sociocultural context, including use of non-textual media to include individuals with low literacy skills, may further enhance education uptake in endemic communities. The use of locally-broadcast radio programs or simple, illustrative printed material such as posters, leaflets and comic books may also add value to educational programs [7, 8, 11, 37], especially in areas where access to smartphones or computers is limited. Some standardized educational posters are available for T .…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of trachoma terminology has been significantly improved in Ethiopian and Malian communities by regularly radio broadcasting trachoma-related public health messages. 18 , 19 These methods of promotion and education could be viable and sustainable on Bubaque, where most families have access to radios 6 and there are daily community radio programs in the local dialect.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2008, radio messages about trachoma have been broadcasted [97]. A 2011 survey on the impact of the radio as a conduit for trachoma health education was conducted with the participation of 391 adults and 687 kids in the Kayes and Segou Regions.…”
Section: Face Washing and Environmental Improvementmentioning
confidence: 99%
“…Two-thirds reported that the children washed their face at least twice daily, and 94% said that they used latrines for the disposal of feces. Yet, there was no significant difference in facial cleanliness of children between those whose caretakers heard the radio messages and those who did not, and the authors concluded that it was still necessary to make sanitation, hygiene, and environmental improvement messages clearer [97]. One potential solution that was an important finding resulting from the previously mentioned study on risk factors in Mali [87] was that the presence of a women's association in the 203 participating villages was significantly, negatively associated with trachoma (OR: 0.55; 95% CI 0.36–0.84), which led to the authors' recommendation that the women's associations be the communications network for a health communication directed at changing behaviors.…”
Section: Face Washing and Environmental Improvementmentioning
confidence: 99%